تأثير إضافة بذور الحلبة وأوراق القراص إلى الخلطات العلفية للفروج على بعض المؤشرات الإنتاجية (Journal of Hama University, 2024)
The aim of this research was to study the effect of adding (Fenugreek seeds and Nettle leaves) to the feed mixtures on some productive indicators in broilers. 180 crossbred chicks (ROSS) were used in the experiment, at the age of one day, without distinguishing between males and females, then they were distributed to seven treatments that included each treatment. 30 chicks differed among themselves in the level of addition of fenugreek seeds and nettle leaves, as treatment T1 was a control that did not add fenugreek seeds and nettle leaves to its diet, treatment T2 added 1% of fenugreek seeds, treatment T3 added 2% of fenugreek seeds, treatment T4 was Adding 1% of nettle leaves, treatment T5 added 2% of nettle leaves, treatment T6 added 0.5% of fenugreek seeds + 0.5% of nettle leaves. The experiment lasted 45 days, and the birds were weighed at the end of the experiment at the age of 45 days. The weights of the birds in each treatment, the weight gain, the amount of feed consumed, the feed conversion coefficient, and the mortality rate in each treatment were calculated.Where the results showed that there were clear significant differences (P < 0.05) in the T6 treatment compared to the control birds and the birds of the rest of the treatments, as the average live weight was (2650.23) g, the weight gain was (2609.07) g, and the amount of feed consumed was (4966), and the feed conversion factor (1,903), while the average live weight was (2420g), the weight gain was (2379) g and the feed conversion factor (2,077) in control birds.